If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.55 = log(x) Multiply glo * x 0.55 = glox Solving 0.55 = glox Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1glox' to each side of the equation. 0.55 + -1glox = glox + -1glox Combine like terms: glox + -1glox = 0 0.55 + -1glox = 0 Add '-0.55' to each side of the equation. 0.55 + -0.55 + -1glox = 0 + -0.55 Combine like terms: 0.55 + -0.55 = 0.00 0.00 + -1glox = 0 + -0.55 -1glox = 0 + -0.55 Combine like terms: 0 + -0.55 = -0.55 -1glox = -0.55 Divide each side by '-1lox'. g = 0.55l-1o-1x-1 Simplifying g = 0.55l-1o-1x-1
| 3x-6x+6=x-5+11 | | -4m-7(6m-4)= | | (7x-4)/5=0 | | 2(12/7)-5= | | -5y^2+8y-3=0 | | 16z+5z=-3 | | 10+11(x)=87 | | 3k^2-9k+5=0 | | (w/5)=20 | | 7z-(2z-8)=-2 | | (X/-2)=(-9) | | (2x-5)=(9x+7) | | 6(1-1x)=11x-2(1x+2) | | 3v^2-8v-5=0 | | (x+1)(x+1)=(x+1)(x+1) | | -3=x/3 | | 7-3x=173 | | (6x-4)-8=12 | | -3=-4+5a-4a | | 7t^2-5t-6=0 | | 16x+3=9x+73 | | -5*a+(-5*b)=5 | | -5/8x=-60 | | ((m^(1/5))/((m^(4/5))(m^-(4)))=m^(a/b) | | 8d^2+6d+1=0 | | 5(.5-3)+3(.5+3)=2(.5)-3 | | 8u^2-9u-3=0 | | 3x^3+33x^2+90x= | | 2m^2+4m+2=0 | | 3x^3+6x=4x^2+8 | | x+2x+2= | | 6(1x-1x)=11x-2(x+2) |